Teaching Practices of Mathematics Teachers in Developing Probe Thinking - Alsulami, Turki Humaid (Journal of Curriculum and Teaching Methodology, 2023)
The research aimed to identify the level of teaching practices of mathematics teachers in developing probe thinking of their students from the point of view of their supervisors, and to achieve this goal, the research followed the descriptive survey method. The researcher prepared a questionnaire, which he applied to a sample consisting of (23) male educational supervisors and (20) female educational supervisors, who are the entire research population in Makkah Educational Region. The results of the research showed that the level of teaching practice of mathematics teachers in developing probe thinking among their students was weak, and that there was a statistically significant difference between the average scores of the research sample in the level of practice and in favor of the female educational supervisors. In the light of the results, the researcher recommended adopting probe thinking as a teaching model, and training mathematics teachers on its skills and implementation mechanisms.